2010
DOI: 10.1161/circulationaha.109.929646
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Cardiomyopathy as a Part of Familial Dilated Cardiomyopathy

Abstract: Background-Anecdotal cases of familial clustering of peripartum cardiomyopathy (PPCM) and familial occurrences of PPCM and idiopathic dilated cardiomyopathy (DCM) together have been observed, suggesting that genetic factors play a role in the pathogenesis of PPCM. We hypothesized that some cases of PPCM are part of the spectrum of familial DCM, presenting in the peripartum period. Methods and Results-We reviewed our database of 90 DCM families, focusing specifically on the presence of PPCM patients. Then, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
146
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 28 publications
2
146
0
9
Order By: Relevance
“…We recently demonstrated a set of mutations in TNNC1 linked to HCM with the potential to disrupt myocardial contractility (23). Before this report, only two mutations in TNNC1 had been linked to DCM (6,7,18). The G159D (6, 7) and Q50R (18) mutations have been shown to segregate among family members.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We recently demonstrated a set of mutations in TNNC1 linked to HCM with the potential to disrupt myocardial contractility (23). Before this report, only two mutations in TNNC1 had been linked to DCM (6,7,18). The G159D (6, 7) and Q50R (18) mutations have been shown to segregate among family members.…”
Section: Discussionmentioning
confidence: 96%
“…Another recent human study identified a mutation in TNNC1 that segregated with familial DCM (including a member with peripartum cardiomyopathy), adding to the genetic evidence of this disease (18). In this study, we present clinical, pedigree, and functional studies of the Y5H, M103I, D145E (this mutation was previ-ously studied as a hypertrophic cardiomyopathy (HCM)-linked mutation), and cTnC I148V genetic variants in human DCM and show that two of these novel rare variants manifested functional properties typical of DCM (decreased Ca 2ϩ sensitivity), accompanied by altered responsiveness to PKA phosphorylation in all the mutants.…”
mentioning
confidence: 99%
“…Despite this, it has been observed that PPCM is seen more frequently in some families and frequently occurs in women with a higher familial incidence of dilated cardiomyopathy (DCM). This suggests that PPCM could be part of wider DCMlike-disorder group 8,9 . The contributing risk factors leading to PPCM include race with a clearly higher incidence and more severe course in afro-american women, higher maternal age, multiple pregnancies, obesity, preeclampsia, hypertension, diabetes, infection, and prolonged use of beta-agonist tocolytics.…”
Section: Introductionmentioning
confidence: 94%
“…В этой связи представляются интересными резуль-таты исследования, проведенного в Нидерландах K. van Spaendock et al [42]. При детальном анализе анамнести-ческих и клинических данных 90 семей больных ДКМП, авторы обнаружили в 5 семьях (6%) случаи ПКМП, что существенно выше частоты этой патологии в общей популяции.…”
Section: роль вирусовunclassified
“…Авторы предполагают, что у женщин с семейной предрасположенностью к ДКМП окислительный стресс, ассоциированный с дородовым и послеродовым периодами, является пусковым фактором развития заболевания. И, тем не менее, подчеркивается, что ука-занный механизм может быть ответственным лишь за часть случаев ПКМП [42].…”
Section: роль вирусовunclassified